Direct diffusion bonding of immiscible tungsten and copper at temperature close to Copper's melting point. (5th January 2018) - Zhang, Jie; Huang, Yuan; Liu, Yongchang; Wang, Zumin
Highlights: Direct diffusion bonding method is a feasible way to construct a metallurgical bonding interface between immiscible W and Cu. The key point of the direct diffusion bonding is that bonding temperatures should be close to copper's melting point. The maximum tensile and bending strengths of the obtained W/Cu joints are about 172 MPa and 232 MPa, respectively. A diffusion occurs between W and Cu and the thickness of the W/Cu diffusion layer is about 22 nm. Graphical abstract: Abstract: In this study, a direct diffusion bonding method is designed to bond tungsten (W) and copper (Cu) without using an interlayer metal at a temperature close to the melting point of copper (TmCu ). The results show that the direct diffusion bonding method is feasible and the key point to a successful connection is that bonding temperatures should be controlled in an effective temperature range 0.81TmCu –0.97TmCu . The most appropriate bonding parameters are that the bonding temperature is 980 °C, the bonding time is 180 min and the bonding pressure is 106 MPa. The maximum tensile and bending strengths of the as-obtained W/Cu joints are 172 and 232 MPa, respectively, which reach a very high level compared to pure copper. The corresponding fractures are ductile. The micro-tests for the W/Cu joint show that diffusion occurs between W and Cu and the thickness of the W/Cu diffusion layer is 22 nm. Through the diffusion, a metallurgical bonding interface has been successfully constructed, which is the essential reason for the high strengths of the W/Cu joint. The diffusion between W and Cu when the bonding temperature is close to TmCu may be induced by the high-temperature structure of Cu, which needs further investigation.